2021
DOI: 10.3390/s21020509
|View full text |Cite
|
Sign up to set email alerts
|

A Self-Diagnosis Method for Detecting UAV Cyber Attacks Based on Analysis of Parameter Changes

Abstract: We consider how to protect Unmanned Aerial Vehicles (UAVs) from Global Positioning System (GPS) spoofing attacks to provide safe navigation. The Global Navigation Satellite System (GNSS) is widely used for locating drones and is by far the most popular navigation solution. This is because of the simplicity and relatively low cost of this technology, as well as the accuracy of the transmitted coordinates. Nevertheless, there are many security threats to GPS navigation. These are primarily related to the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Thus, for example, the speed of the engines and the flight altitude may not be related to the attack but may change due to gusts of wind. For an unambiguous definition of an attack, it is necessary to analyze several cyber-physical parameters at once and determine the degree of their deviation [42].…”
Section: Intrusion Detection Methods For Uavsmentioning
confidence: 99%
“…Thus, for example, the speed of the engines and the flight altitude may not be related to the attack but may change due to gusts of wind. For an unambiguous definition of an attack, it is necessary to analyze several cyber-physical parameters at once and determine the degree of their deviation [42].…”
Section: Intrusion Detection Methods For Uavsmentioning
confidence: 99%
“…Our analysis of the normalized cyber-physical parameters showed that the probability distribution of the victim and the normal state is often close to each other, but the abnormal state is significantly different [ 27 ]. To measure the difference between function distributions, the Kullback-Leibler entropy measure is used.…”
Section: Methodsmentioning
confidence: 99%
“…Relative entropy is a measure of the distance between two distributions [28]. In statistics, it appears as the expected logarithm of the likelihood ratio [27]. The relative entropy D (p||q) is the measure of inefficiency if the distribution is assumed to be q when the true distribution is equal to p. For example, if you know the true distribution p of a random variable, you can construct a code with an average description length H (p).…”
Section: The Methods Of Detecting Anomalies Based On Entropy In the Sensor Systemmentioning
confidence: 99%
“…The studies were also carried out on the required power, and requirements for the content of the generated signal. The characteristics of determining the fact of an ongoing GPS spoofing attack were also proposed [28].…”
Section: Methodsmentioning
confidence: 99%